A comparative study of the evolution of tourism policy in Spain and Portugal - Almeida-García, Fernando (My University, 2014)
The purposes of this study are to analyze and compare the way in which tourism policy has evolved in Spain and Portugal. Our study covers an extensive period of time, enabling the similarities and differences between the two processes and the effects of the main factors involved to be highlighted phase by phase. We start by looking at the genesis of tourism authorities, whose principal objective was to promote the countries and improve their external image. We will then see how the onset of mass tourism led to changes in strategy, which now sought to maximize revenue in order to fund national development. The third phase will deal with the restructuring of the countries' respective tourism authorities, whereby policies and planning were tailored to accommodate the changes that had occurred in the sector. We will conclude by suggesting a series of topics for debate, notably the Latin model of tourism development.
The author is grateful for the financial support received from the project (CSO2012-30840) Geographies of crisis: analysis of urban-tourist areas of the Balearic Islands, Costa del Sol and major tourist destinations in the Caribbean and Central America, National Plan R + D, Ministry of Science and Innovation, Spain. I would like to thank Ph.D. Licinio Cunha (University Lusofona of Lisbon), Ph.D. Enrique Navarro, Ph.D. Laura Moniche and Ph.D Antonio Mora (University of Malaga), for their assistance, suggestions and criticism.
Keywords: Portugal - Política turística; España - Política turística; Tourism policy; Development; Spain; Portugal; Tourism phases